Gamification: Classification of the Users Based on Player Types and Motivations - Tunggawan, Edwin (Swiss German University, 2018)
A comparison between two methods to understand the players’ behavior in games. The first one is the player types model by Richard Bartle, and the second is the motivations model by Nick Yee. It’s concluded that Yee’s model is better when the developers need a more detailed understanding on their users, while Bartle’s model is better to use when the developers need to classify the users in a quicker and simpler way.